2018
DOI: 10.3390/ijms19124090
|View full text |Cite
|
Sign up to set email alerts
|

How Glucocorticoids Affect the Neutrophil Life

Abstract: Glucocorticoids are hormones that regulate several functions in living organisms and synthetic glucocorticoids are the most powerful anti-inflammatory pharmacological tool that is currently available. Although glucocorticoids have an immunosuppressive effect on immune cells, they exert multiple and sometimes contradictory effects on neutrophils. From being extremely sensitive to the anti-inflammatory effects of glucocorticoids to resisting glucocorticoid-induced apoptosis, neutrophils are proving to be more co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
152
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(166 citation statements)
references
References 86 publications
(90 reference statements)
12
152
0
2
Order By: Relevance
“…Consistently, as previously reported, steroids can induce increased absolute neutrophil count (ANC) [ 19 , 20 , 21 ], and it has been even associated with the polarization of macrophages to M2 macrophages, with pro-tumoral functions [ 22 ]. Thus, the global impact of steroids on the immune context of the patients should be further explored.…”
Section: Discussionsupporting
confidence: 73%
“…Consistently, as previously reported, steroids can induce increased absolute neutrophil count (ANC) [ 19 , 20 , 21 ], and it has been even associated with the polarization of macrophages to M2 macrophages, with pro-tumoral functions [ 22 ]. Thus, the global impact of steroids on the immune context of the patients should be further explored.…”
Section: Discussionsupporting
confidence: 73%
“…The relationship between glucocorticoids and T-lymphocytes is complex, but there appears to be a consensus in the literature that glucocorticoids lead to thymocyte apoptosis, with subsequent decrease in immature T-cell counts [38][39][40][41] and skewing of the T-cell response toward Th2 [41][42][43] . In addition, we hypothesize that corticosteroid treatment in mice reduced migration of neutrophils from the blood into the lungs, coupled with reductions in superoxide and reactive oxygen species, which may have allowed M. abscessus to proliferate unimpaired [44][45][46][47] . No animal model is able to comprehensively simulate all aspects of human infection and pathology, nor does any one model meet all investigative goals within.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, corticosteroids have proinflammatory effects in neutrophils. Corticosteroids are generally thought to weakly suppress neutrophilic inflammation, although several research groups reported them to inhibit the neutrophil respiratory burst and interfere with neutrophil recruitment ( Strausbaugh and Rosen, 2001 ; Ronchetti et al, 2018 ; Ricci et al, 2019 ). For instance, corticosteroids do not improve neutrophilic inflammation in corticosteroid-resistant asthma or COPD ( Yang et al, 2012 ; Ronchetti et al, 2018 ).…”
Section: Drugs Targeting Neutrophils For Covid-19 Associated Ardsmentioning
confidence: 99%